Synthesis and Characterization of Magnesium Ferrite Materials - Sabah Mohammed Ali Ridha; Ghead Khalaf Salman (Engineering and Technology Journal, 2014)
NiZnMg-Ferrite Nano ceramics were prepared by using sol-gel auto combustion method, these ferrites then pelletized and sintered at different temperatures (1000, 1100 and 1200 0C). Ferrite samples showed spinel structure and inherent ‎properties of high electrical resistivity, low electrical losses and high theoretical ‎densities. Therefore, these ferrites have a potential candidate for high frequency applications. The electrical and structural ‎properties of Ni0.7-yZn0.3MgyFe2O4 (where; y= 0, 0.1, 0.2 and 0.3) were studied and that shows an effect of chemical composition ‎on the electrical, structural, and physical properties depending on Mg content in the Ferrite. Chemical phase analysis carried out by x-ray diffraction spectrum ‎confirms the formation of ferrite Nanopowders with size (22.6 nm), and found that the lattice parameters and particle sizes increase, while theoretical density and porosity ‎decreases with increasing of Mg content in the NiZnMg Ferrites. Resistivity of all samples has been measured at temperatures in the range of ‎‎ (300-540 K), which decreases with increasing of temperatures like ‎a semiconductor behavior.